A Self‐Powered CNT–Si Photodetector with Tuneable Photocurrent. (9th November 2022) - Pelella, Aniello; Capista, Daniele; Passacantando, Maurizio; Faella, Enver; Grillo, Alessandro; Giubileo, Filippo; Martucciello, Nadia; Di Bartolomeo, Antonio
Abstract: A photodetector with bias‐tuneable current is realized by adding a film of single‐walled carbon nanotubes (CNT), forming a CNT/Si3 N4 /Si capacitor, to a prefabricated Pt–Ti/Si3 N4 /Si metal–insulator–semiconductor (MIS) diode. Electrical characterization of the entire device is performed to extract the temperature‐dependent ideality factor and Schottky barrier height in the framework of the thermionic emission theory. The CNT/Si3 N4 /Si capacitor increases the reverse current of the parallel Pt–Ti/Si3 N4 /Si MIS diode by adding a Fowler–Nordheim tunneling current at high reverse voltage bias. This feature endows the photodetector with two different photocurrent levels, photoresponsivity up to 370 mA W −1 and external quantum efficiency up to 50% at 950 nm wavelength. The device also shows a different photoresponse when light is focused on the CNT/Si3 N4 /Si region or around the Pt–Ti/Si3 N4 /Si structure. The photodetector can also be used as an optoelectronic Boolean logic device, in which the applied voltage bias and the incident light are the two input signals, and the photocurrent is the output. Furthermore, light generates a photocurrent at zero voltage and a photovoltage at zero current, making the device a self‐powered photodetector. Abstract : A photodetector is realized by adding single‐walled carbon nanotubes (CNT), forming a CNT/Si3 N4 /Si capacitor, to a prefabricated Pt–Ti/Si3 N4 /Si metal–insulator–semiconductor (MIS) diode. This layout endows the photodetector with a bias‐tunable photocurrent and a different photoresponse when light is focused on the capacitor or around the MIS diode. These features make it suitable for several applications, like optoelectronic Boolean logic devices.